Evaluation of Cochlear Symptoms in Migraine Patients without Vestibular Migraine and/or Ménière’s Disease - Valeria Gambacorta; Giampietro Ricci; Alessandra D’Orazio; Davide Stivalini; Irene Baietta; Vito Enrico Pettorossi; Mario Faralli (Audiology Research, 2023)
Migraine pathogenic pathways may selectively target the cochlea. A qualitative and quantitative analysis of cochlear symptoms in migraine patients without vestibular migraine and/or Méniere’s disease was conducted. We examined 60 consecutive patients with history of cochlear symptoms, including fullness, tinnitus, and hearing loss. Patients were divided into two groups based on migraine history: M (migraine) and nM (no migraine). The incidence of migraine was compared to a homogeneous control group with dysfunctional and inflammatory dysphonia without cochlear symptoms. The type, time of onset, recurrence, bilaterality of symptoms, and hearing threshold were analyzed. The incidence of migraine was significantly higher (p = 0.04) in patients with cochlear symptoms than in the control group. The onset of symptoms is significantly earlier (p < 0.05) in the presence of migraine. The fullness, recurrence, and bilaterality of symptoms are associated with migraine in a statistically significant way (p < 0.05). Pure tone audiometry shows a statistically significant increase in the hearing threshold (500–1000 Hz) in group M. Based on developing findings, cochlear migraine may be considered as a novel clinical entity, like vestibular migraine. It would be the expression, in the absence of vertiginous symptoms, of a selective suffering of the anterior labyrinth by known operating mechanisms of migraine.